2012
DOI: 10.1111/j.1750-2659.2012.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent influenza virus infection and tuberculosis in patients hospitalized with respiratory illness in Thailand

Abstract: Thailand, where influenza viruses circulate year‐round, is one of 22 WHO‐designated high‐burden countries for tuberculosis (TB). Surveillance for hospitalized respiratory illness between 2003 and 2011 revealed 23 (<1% of 7180 tested) with concurrent influenza and TB. Only two persons were previously known to have TB suggesting that acute respiratory illness may bring patients to medical attention and lead to TB diagnosis. Influenza/TB was not associated with higher disease severity or mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Higher TB death rates were noted in winter months (coinciding with seasonal influenza outbreaks), which led to the suggestion of PTB being an independent risk factor for influenza-associated mortality [ 10 ]. In contrast, few studies suggested no association between influenza coinfection and PTB's progression or severity [ 20 , 21 ]. One murine model demonstrated that although influenza infection increased the IFN- γ secretion, it had little effect on bacterial load in chronically infected mice with BCG [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher TB death rates were noted in winter months (coinciding with seasonal influenza outbreaks), which led to the suggestion of PTB being an independent risk factor for influenza-associated mortality [ 10 ]. In contrast, few studies suggested no association between influenza coinfection and PTB's progression or severity [ 20 , 21 ]. One murine model demonstrated that although influenza infection increased the IFN- γ secretion, it had little effect on bacterial load in chronically infected mice with BCG [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from 1999–2009 in South Africa mirrors these findings and shows that for those both under and over 65 the relative risk of influenza-associated mortality increased [ 28 ]. However, we should also note that a study of Thai hospitalized patients presenting with acute respiratory illness did not find an increased risk of clinical worsening or mortality in PTB patients co-infected with influenza virus [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Thailand did not identify an increased risk of severe outcomes or mortality in patients co-infected with tuberculosis and seasonal influenza when compared to tuberculosis and influenza single infection [ 18 ]. The number of patients co-infected with influenza and tuberculosis in this study were, however, small, and patients with a more chronic presentation were not enrolled in the surveillance system.…”
Section: Discussionmentioning
confidence: 99%